Forecasting Population of Madiun Regency Using ARIMA Method - Farida, Yuniar; Farmita, Mayandah; Ulinnuha, Nurissaidah; Yuliati, Dian (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2022)
The high population growth of the Madiun Regency can cause population density that can have implications for other problems, both in terms of social, economic, welfare, security, land availability, availability of clean water, and food needs. This study aims to predict the population growth of Madiun Regency using the ARIMA method. The ARIMA (Autoregressive Integrated Moving Average) method is popular for forecasting time series data, which is reliable because the calculation process is done gradually. This study uses annual population data of Madiun Regency from 1983 to 2021 and produces an ARIMA forecasting model (0,2,1) with a MAPE value of 8.42%. The results of this study are expected to be used as information from the Madiun Regency government in anticipating the emergence of problems caused by the population level of Madiun Regency in the future.